CITRA POLITIKUS ARTIS DALAM VLOG DESY RATNASARI: PERSPEKTIF LAMBANG, BAHASA DAN OPINI PUBLIK - Nurhablisyah (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
This study analyzes the image of artist politicians in Desy Ratnasari's Vlog in the perspective of symbols, language, and public opinion. This research is qualitative research used to analyze Desy Ratnasari's Vlog. The analytical method used is qualitative content analysis. The research findings are the image that is captured by the community and form public opinion, in this case the audience is Desy Ratnasari as a celebrity politician who is smart, assertive, simple, cares about the environment and is religious. As a Muslim and also the chairman of the West Java PAN DPW, Desy often shares da'wah messages in his videos, especially reminding his audience to always be healthy, do good and protect the environment. If the image shown in front of the camera corresponds to the actual situation outside the camera, then someone has consistently performed his duty as a servant. Because the invitation to kindness is not only to straighten others out but for yourself, thus this can move others to do the same.